Assessment of "Grain for Green" Program in ethnic poor areas in China - Long, Qingsong; Shivakoti, Ganesh P.; Routray, Jayant Kumar; Shrestha, Rajendra Prasad; Ford Foundation International Fellowship Program, IFP-Ford Foundation; Asian Institute of Technology Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2007)
This paper uses the viewpoint of economic externality to assess the policy of "grain for green" program (GGP); it tries to find some effective measures to control economic externality. In order to reach the goal, to grasp the status of farmers' livelihood is important, which is conducive to understand the relationship among ecological construction, compensation and livelihood; to master GGP's executive status is necessary, which can help us to understand existent issues about implementing policy; to hold the performance status of tree growth is radical, which can contribute to us to appraise project's ecological benefit-namely, project whether has appeared the positive externality. Author chooses four factors to analyses economic externality of GGP, points out some measures to control externality at different issues. In the paper, author found that different issue would take different measure to control its externality, and different period would adopt different externality theory as guidance to control externality, subsequently combining several measures to resolve externality issues have better efficiency and far reaching. On the other hand, property right plays an important role in forestry reform. Finally GGP policy would be institutionalized, which contributes to GGP to keep positive externality in ethnic poor areas
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science in Natural Resources Management, School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 2007
Keywords: Ecological assessment (Biology) -- China; Forest conservation -- Evaluation -- China; Grain for Green Program -- Evaluation -- China